MENINGKATKAN KETERAMPILAN PROSES SAINS MELALUI PENERAPAN METODE EKSPERIMEN PADA ANAK USIA 5-6 TAHUN DI TK PELITA HATI DESA LUBUK TERENTANG KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Ilyendri, Neltiva; ', Wilson; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack:        This research aims to determine the increase science process skills through the application of the experimental method in children aged 5-6 years in kindergarten Pelita Hati Lubuk Terentang District of Gunung Toar Regency Kuantan Singingi. The population of this study is children aged 5-6 years in kindergarten Pelita Hati. The study sample as many as 16 children. Type of research is classroom action research. The study consisted of two cycles where each cycle there are three meetings. The research design consisted of four events in a repeating cycle of planning, action, observation, and reflection. Instrument of collecting data in this study was the observation sheets science process skills of children. Data collection techniques were used that observation method in which the data were analyzed descriptively. Based on descriptive analysis is obtained there is increasing science process skills of children aged 5-6 years in kindergarten Pelita Hati. It is evident from the increase before the cycle to cycle 1 of 27.1%, an increase from cycle 1 to cycle 2 of 56.1% and an increase of the total before the cycle to cycle 2 that is equal to 98.5%. From the above analysis it can be concluded that the application of the experimental method is effective to improve science process skills at the age of 5-6 years in kindergarten Pelita Hati village of Lubuk Terentang District of Mount Toar Regency Kuantan Singingi.